1997
DOI: 10.1007/s004310050673
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload and urinary lysosomal enzyme levels in β-thalassaemia major

Abstract: Iron overload resulted in increased urinary levels of the lysosomal enzyme NAG which has been proposed as an early marker of kidney damage. Reduction of iron load, achieved by regular desferrioxamine infusion, resulted in normalisation of the urinary enzyme levels. Thus kidney lysosomes appear to be a target and possibly a mediator of iron toxicity in this tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
25
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 22 publications
4
25
1
2
Order By: Relevance
“…[8][9][10] The mechanism of injury is mediated by mitochondrial stress in proximal tubular cells, as evidenced by increased efflux of cytochrome C, release of lactate dehydrogenase, and reduction in adenosine triphosphate. 11,12 This pathologic and experimental evidence is supported by clinical studies showing a good correlation between serum ferritin levels and markers of tubular toxicity, 13,14 and by reversal of tubular defects after iron chelation therapy. 14,15 Chronic anemia and hypoxia are also associated with oxidative stress, lipid peroxidation, and functional abnormalities in tubular cells.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…[8][9][10] The mechanism of injury is mediated by mitochondrial stress in proximal tubular cells, as evidenced by increased efflux of cytochrome C, release of lactate dehydrogenase, and reduction in adenosine triphosphate. 11,12 This pathologic and experimental evidence is supported by clinical studies showing a good correlation between serum ferritin levels and markers of tubular toxicity, 13,14 and by reversal of tubular defects after iron chelation therapy. 14,15 Chronic anemia and hypoxia are also associated with oxidative stress, lipid peroxidation, and functional abnormalities in tubular cells.…”
mentioning
confidence: 91%
“…11,12 This pathologic and experimental evidence is supported by clinical studies showing a good correlation between serum ferritin levels and markers of tubular toxicity, 13,14 and by reversal of tubular defects after iron chelation therapy. 14,15 Chronic anemia and hypoxia are also associated with oxidative stress, lipid peroxidation, and functional abnormalities in tubular cells. 16,17 Damage to the proximal tubule and volume increases of the peritubular space were also demonstrated in one study on anemic rats.…”
mentioning
confidence: 91%
“…Similarly, iron overload in rats led to mild proteinuria with iron deposits in glomeruli, proximal tubules, and interstitium associated with glomerulosclerosis, tubular atrophy, and interstitial fibrosis (38). Several studies reported correlation between serum ferritin levels and markers of tubular toxicity, which iron chelation therapy reversed (7,39). Other studies have shown renal tubular abnormalities related to duration of chelation, duration of transfusions, amount of transfusions, and body iron content, as measured by magnetic resonance imaging (5,7,8).…”
Section: Discussionmentioning
confidence: 99%
“…4 Kelebihan besi dan anemia kronik merupakan faktor utama penyebab abnormalitas tubulus ginjal. 1,3,5,6 Pada kasus TßM, beberapa penelitian tentang disfungsi ginjal memperlihatkan bahwa pemeriksaan biokimia rutin tidak dapat mendeteksi dini kerusakan tubulus ginjal. 7,8 Penelitian lain membuktikan bahwa N-acetyl-β-D-glucosaminidase (NAG) merupakan pemeriksaan yang paling dapat diandalkan untuk mendeteksi dini kerusakan tubulus ginjal pada TßM dibandingkan dengan pemeriksaan yang lain.…”
unclassified
“…7,8 Penelitian lain membuktikan bahwa N-acetyl-β-D-glucosaminidase (NAG) merupakan pemeriksaan yang paling dapat diandalkan untuk mendeteksi dini kerusakan tubulus ginjal pada TßM dibandingkan dengan pemeriksaan yang lain. 2,9,5,10,11 Luasnya pemakaian kelasi besi per oral, terma s uk di Indonesia, menuntut banyak peneliti melaku kan penelitian mengenai manfaatnya dalam mengura ngi kelebihan besi dalam tubuh, tetapi disisi lain juga dituntut untuk melakukan penelitian mengenai efektivitasnya dalam mempertahankan fungsi organ termasuk ginjal. Sampai saat ini, penelitian mengenai hubungan penggunaan kelasi besi oral dengan fungsi tubulus ginjal belum ditemukan.…”
unclassified